Utilization of the Subak Jatiluwih Landscape as a Tourism Object: Tourist Perceptions and the Impact on Village Income - Prastyadewi, Made Ika; Parwita, Gede Bayu Surya; Pramandari, Putu Yusi (Universitas Dian Nuswantoro Semarang, 2023)
The growing development of the tourism sector impacts increasing land conversion, which results in a reduction in productive agricultural land and the threat of subak as an agricultural institution based on local wisdom in Bali. The development of the tourism sector has eroded the existence of subak due to the high economic value of converting agricultural land to non-agricultural functions. If this condition continues, the existence of subak as a form of local wisdom in the agricultural sector in Bali will become extinct. Moreover, the subak cultural landscape in Bali has been recognized by UNESCO as a World Cultural Heritage. The heritage includes four sites (areas) which all form one unit.This study aims to analyze the use of the Jatiluwih subak landscape as a tourist object by focusing on the problem of tourists’ perceptions of the subak Jatiluwih landscape and the impact of these tourism activities on village income. The research was conducted on the Subak Jatiluwih Landscape as a WBD icon. The approach used is a quantitative approach using primary and secondary data. The sample in this study was taken by interview method and documentation study, which was then analyzed descriptively. The analysis results show an increase in the number of tourist visits every year where tourists think that an interesting tourist object is a place that has uniqueness. Tourism activities also positively impacted the village economy, where the local traditional village managed and fairly shared income from entrance tickets to tourist objects.